Propriedades físico-química e antibacteriana de medicações intracanal a base de hidróxido de cálcio e óxido de zinco micro e nanoparticulados - Aguiar, Alana Priscila Souza [UNESP] (2014)
Enterococcus faecalis presents high resistance to intracanal medications. The use of nanoparticulate substances and the association with chlorhexidine may interfere with the effectiveness of the medication. The aim of this study was to evaluate pH and antibacterial activity of medications based microparticulate (micro) or nanoparticles (nano) calcium hydroxide (CH) and zinc oxide (ZnO) associated or without chlorhexidine 0.4% against Enterococcus faecalis. Medications were analyzed: HC / ZnO micro; HC / ZnO nano; HC / ZnO micro + Chlorhexidine 0.4%; HC / ZnO nano + Chlorhexidine 0.4%. Polyethylene glycol 400 was used as vehicle. The antibacterial activity against E. faecalis was evaluated by three in vitro studies: Study of Diffusion in Agar, Testing of Direct Contact in planktonic cells and through induced biofilm in root canals of human teeth. The analysis of pH was determined using bovine teeth of diffusion and dissociation of polyethylene tubes. The results of studies obtained were submitted to ANOVA and Tukey or Kruskal-Wallis and Dunn, with a significance level of 5%. The results of the agar diffusion test showed that the HC / ZnO nano and with 0.4% chlorhexidine medication were more effective. In Direct Contact medication with chlorhexidine showed increased activity after 30 seconds are all eliminated Enterococcus faecalis after 1 minute. The diffusion test for bovine dentin showed higher pH increase for nanoparticulate medication in periods 1 and 7 days (p <0.05). All medications pH increase promoted similarly (p> 0.05) in test tubes of polyethylene. The evaluation showed that in root canals medication so effective in collecting after their removal, but the final collection medications with chlorhexidine showed higher bacterial reduction (p <0.05). It is concluded that the nanoparticles of calcium hydroxide and zinc oxide promote greater dentinal diffusion and high pH in the...(Complete abstract electronic acess below)